Residual flexibility in the topologically constrained multivalent complex between the GKAP scaffold and LC 8 hub proteins - Nagy-Kanta Eszter; Kálmán Zsófia Etelka; Tossavainen Helena; Juhász Tünde; Farkas Fanni; Hegedüs József; Keresztes Melinda; Beke‐Somfai Tamás; Gáspári Zoltán; Permi Perttu; Péterfia Bálint (FEBS JOURNAL, 2025)
Guanylate kinase‐associated protein (GKAP) is a large postsynaptic scaffold protein bearing two closely spaced noncanonical binding sites for the bivalent dynein light chain LC8 hub protein. This might allow the formation of heterogeneous complexes with different sizes and topologies. Here, we show that a well‐defined hexameric complex is formed, composed of two GKAP molecules and two LC8 dimers. Using nuclear magnetic resonance (NMR) spectroscopy, we demonstrate that the LC8‐binding segment of GKAP is intrinsically disordered and the flexibility of the linker region is largely retained even in the complex form. Molecular dynamics calculations suggest that, besides the tightly bound residues, the hexamer also exhibits several dynamically interchanging interactions, and that the two LC8 dimers might interact with each other. The flanking regions of the two binding sites on GKAP exhibit different interaction patterns, hinting at additional contacts that might explain the fixed stoichiometry of the assembly. Our results demonstrate that constrained stoichiometry can coexist with substantial flexibility in a multivalent system.